We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
48
1
avatar

Find the distance from the point \((1,2,3)\) to the line described by \(\begin{pmatrix} 6 \\ 7 \\ 7 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix}.\)

 Sep 5, 2019

Best Answer 

 #1
avatar+23086 
+3

Find the distance from the point \((1,2,3)\) to the line described by \(\begin{pmatrix} 6 \\ 7 \\ 7 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix}\).

\(\text{Let point $\vec{p} = \begin{pmatrix} 1 \\ 2 \\ 3 \end{pmatrix} $} \\ \text{Let line $\vec{x} = \begin{pmatrix} 6 \\ 7 \\ 7 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} $} \\ \text{Let direction vector $\vec{r} = \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} $} \)

 

\(\begin{array}{|rcll|} \hline \left( \vec{x}-\vec{p} \right) \cdot \vec{r} &=& 0 \quad | \quad (\vec{x}-\vec{p}) \perp \vec{r} \\\\ \Bigg(\begin{pmatrix} 6 \\ 7 \\ 7 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix}-\begin{pmatrix} 1 \\ 2 \\ 3 \end{pmatrix} \Bigg) \cdot \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} &=& 0 \\\\ \Bigg(\begin{pmatrix} 6-1 \\ 7-2 \\ 7-3 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} \Bigg) \cdot \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} &=& 0 \\\\ \Bigg(\begin{pmatrix} 5 \\ 5 \\ 4 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} \Bigg) \cdot \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} &=& 0 \\\\ \begin{pmatrix} 5+3t \\ 5+2t \\ 4-2t \end{pmatrix} \cdot \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} &=& 0 \\\\ 3(5+3t)+2(5+2t)-2(4-2t)&=& 0 \\ 15+9t+10+4t-8+4t &=& 0 \\ 17+17t &=& 0 \\ 17t &=& -17 \quad | \quad : 17 \\ \mathbf{ t } &=& \mathbf{ -1 } \\ \hline \end{array}\)

 

\(\text{foot (of a perpendicular):}\)

\(\begin{array}{|rcll|} \hline \vec{x}_{f} &=& \begin{pmatrix} 6 \\ 7 \\ 7 \end{pmatrix} + (-1) \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} \quad | \quad t=-1 \\\\ &=& \begin{pmatrix} 6-3 \\ 7-2 \\ 7+2 \end{pmatrix} \\\\ \mathbf{ \vec{x}_{f} } &=& \begin{pmatrix} \mathbf{3} \\ \mathbf{5} \\ \mathbf{9} \end{pmatrix} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \vec{PL} &=& \vec{x}_{f} - \vec{p} \\\\ &=& \begin{pmatrix} 3\\ 5 \\ 9\end{pmatrix} - \begin{pmatrix} 1 \\ 2 \\ 3 \end{pmatrix} \\\\ &=& \begin{pmatrix} 3-1\\ 5-2 \\ 9-3\end{pmatrix} \\\\ \mathbf{\vec{PL}} &=& \begin{pmatrix} \mathbf{2}\\ \mathbf{3} \\ \mathbf{6}\end{pmatrix} \\ \hline \end{array}\)

 

\(\text{distance} = |\vec{PL}|\)

\(\begin{array}{|rcll|} \hline |\vec{PL}| &=& \sqrt{2^2+3^2+6^2} \\ &=& \sqrt{4+9+36} \\ &=& \sqrt{49} \\ \mathbf{|\vec{PL}|} &=& \mathbf{7} \\ \hline \end{array}\)

 

The distance from the point \((1,2,3)\) to the line is 7.

 

laugh

 Sep 6, 2019
 #1
avatar+23086 
+3
Best Answer

Find the distance from the point \((1,2,3)\) to the line described by \(\begin{pmatrix} 6 \\ 7 \\ 7 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix}\).

\(\text{Let point $\vec{p} = \begin{pmatrix} 1 \\ 2 \\ 3 \end{pmatrix} $} \\ \text{Let line $\vec{x} = \begin{pmatrix} 6 \\ 7 \\ 7 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} $} \\ \text{Let direction vector $\vec{r} = \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} $} \)

 

\(\begin{array}{|rcll|} \hline \left( \vec{x}-\vec{p} \right) \cdot \vec{r} &=& 0 \quad | \quad (\vec{x}-\vec{p}) \perp \vec{r} \\\\ \Bigg(\begin{pmatrix} 6 \\ 7 \\ 7 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix}-\begin{pmatrix} 1 \\ 2 \\ 3 \end{pmatrix} \Bigg) \cdot \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} &=& 0 \\\\ \Bigg(\begin{pmatrix} 6-1 \\ 7-2 \\ 7-3 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} \Bigg) \cdot \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} &=& 0 \\\\ \Bigg(\begin{pmatrix} 5 \\ 5 \\ 4 \end{pmatrix} + t \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} \Bigg) \cdot \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} &=& 0 \\\\ \begin{pmatrix} 5+3t \\ 5+2t \\ 4-2t \end{pmatrix} \cdot \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} &=& 0 \\\\ 3(5+3t)+2(5+2t)-2(4-2t)&=& 0 \\ 15+9t+10+4t-8+4t &=& 0 \\ 17+17t &=& 0 \\ 17t &=& -17 \quad | \quad : 17 \\ \mathbf{ t } &=& \mathbf{ -1 } \\ \hline \end{array}\)

 

\(\text{foot (of a perpendicular):}\)

\(\begin{array}{|rcll|} \hline \vec{x}_{f} &=& \begin{pmatrix} 6 \\ 7 \\ 7 \end{pmatrix} + (-1) \begin{pmatrix} 3 \\ 2 \\ -2 \end{pmatrix} \quad | \quad t=-1 \\\\ &=& \begin{pmatrix} 6-3 \\ 7-2 \\ 7+2 \end{pmatrix} \\\\ \mathbf{ \vec{x}_{f} } &=& \begin{pmatrix} \mathbf{3} \\ \mathbf{5} \\ \mathbf{9} \end{pmatrix} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \vec{PL} &=& \vec{x}_{f} - \vec{p} \\\\ &=& \begin{pmatrix} 3\\ 5 \\ 9\end{pmatrix} - \begin{pmatrix} 1 \\ 2 \\ 3 \end{pmatrix} \\\\ &=& \begin{pmatrix} 3-1\\ 5-2 \\ 9-3\end{pmatrix} \\\\ \mathbf{\vec{PL}} &=& \begin{pmatrix} \mathbf{2}\\ \mathbf{3} \\ \mathbf{6}\end{pmatrix} \\ \hline \end{array}\)

 

\(\text{distance} = |\vec{PL}|\)

\(\begin{array}{|rcll|} \hline |\vec{PL}| &=& \sqrt{2^2+3^2+6^2} \\ &=& \sqrt{4+9+36} \\ &=& \sqrt{49} \\ \mathbf{|\vec{PL}|} &=& \mathbf{7} \\ \hline \end{array}\)

 

The distance from the point \((1,2,3)\) to the line is 7.

 

laugh

heureka Sep 6, 2019

22 Online Users

avatar